170 Patterns of recurrence after robotic-assisted radical hysterectomy (RRH) for early stage cervical cancer (CC). (18th September 2019) - Fitzsimmons, C; Stephens, A; Kennard, J; Manyam, M; Pepe, J; DeCoff, K; Ahmad, S; McKenzie, N; Kendrick, J; Holloway, R
Abstract : Objectives: To evaluate the recurrence patterns of early CC following RRH. Methods: Patients with early-stage CC (4/2007–12/2017) who underwent RRH using a uterine manipulator were evaluated. Inclusion criteria: > one year follow-up, adenocarcinoma or squamous carcinoma, stage IA2 or IB1 using FIGO-2014 guidelines, and pathologic tumor size (TS) of ≥4 cm. Results: 144 RRH patients were identified and 90 met inclusion criteria. Baseline characteristics included: TS ≥2 cm 42 (47%) and adenocarcinoma 40 (44%). There were 7 (7.8%) recurrences with median time to recurrence of 12±8.3 months. All recurrences had TS ≥2 cm (median 2.7±0.7 cm). Of the 42 cases with TS ≥2 cm, 14 had adenocarcinoma with 5 (36%) recurrences compared to 28 squamous with 2 (7%) recurrences ( p =0.057). Three recurrences had carcinomatosis with mean RFS and OS of 5.3±2.3 and 28.3±30.9 months compared to 17.8±6.3 and 80.6±48.6 months for cases with local/pulmonary metastasis (n=4). RFS with carcinomatosis was less than RFS for local/pulmonary ( p =0.014). Six recurrences occurred within the first 10 RRH cases per surgeon. Conclusions: Early-stage CC treated with RRH appears to have a unique pattern of recurrence in some cases with carcinomatosis that results in shortened RFS. Recurrences were associated with adenocarcinoma, TS ≥2 cm, and first 10 cases of surgeon experience. Carcinomatosis may be related to negative insufflation following colpotomy, requiring a new strategy that isolates the cervical tumor prior to colpotomy.